Effects of varied starting block angle for the start performance in competitive swimming. Differences of effects between the grab start and the track start - Takeda, T.; Takagi, H.; Tsubakimoto, S. (Japanese Journal of Sciences in Swimming and Water Exercise, 2009)
The purpose of this study was to investigate effects of the varied starting block angle for the start performance in competitive swimming. Ten well-trained college swimmers participated in this study. They performed twice at each 4 types of swim-start trials which were GS (grab start) with 7.5 and 10 degrees of block angle, TS (track start) with 7.5 and 10 degrees. The trials were recorded by high-speed camera (125Hz). Joint motions were calculated by using 2D-DLT methods. Comparisons of kinematical variables were performed by using the two-way repeated-measures analysis (block angle and start technique) of variance. Significant main effect of the block angle were observed in the horizontal and resultant take-off velocity (7.5deg < 10deg) and the entry angle (7.5deg > 10deg). Significant main effects of the start technique were observed block time (GS > TS), coordinates of center of gravity at the takeoff (horizontal GS > TS, vertical GS < TS), the body angle (GS < TS) and the entry angle (GS > TS). Significant interaction were not observed in each variable. These results suggested that an increase of the block angle and using of track start resulted in an advantage for start performance until water entry.